Given differential equation is "y'' -2y' +y = 4x^2 - 1 + \\frac{e^x}{x}"
Auxiliary equation is "m^2 - 2m + 1 = 0 \\implies m =1,1"
so "y = C_1e^x+C_2xe^x"
Let us solve for ("4x^2-1)" by undetermined coefficients and for "\\frac{e^x}{x}" by variation of parameters
(a) undetermined coefficients:
let "y = Ax^2 +Bx+C" be solution of the equation "y'' -2y' +y = 4x^2 - 1"
then differentiating y first and second time with respect to x, and putting in differential equation, then equation will be ,
"2A-4Ax-2B+Ax^2 +Bx+C = 4x^2-1 \\implies A = 4, B=16, C=23"
then "y = C_1e^x+C_2xe^x+ 4x^2 +16x+23"
(b) method of variation of parameters
Differential equation is "y'' -2y' +y = \\frac{e^x}{x}"
since "y = C_1e^x+C_2xe^x" for auxiliary equation
Here "u = e^x, v=xe^x, R =\\frac{e^x}{x}"
Then W, Wronskian of u and v will be
"W = \\begin{vmatrix}\n e^x & xe^x \\\\\n e^x & e^x(x+1)\n\\end{vmatrix} = e^{2x}"
then "P.I. = -u\\int\\frac{vR}{W}dx + v\\int\\frac{uR}{W}dx"
"P.I. = e^x\\int\\frac{xe^xe^x}{xe^{2x}}dx + xe^x\\int\\frac{e^{2x}}{xe^{2x}}dx"
"P.I. = -e^x\\int dx + xe^x\\int \\frac{dx}{x} = xe^x(ln(x) - 1)"
Hence, final solution of the equation will be
"y = C_1e^x+C_2xe^x+ 4x^2 +16x+23 + xe^x(ln(x)-1)"
Comments
Leave a comment